The critical role of informed consent for doctors and patients in the community - Yuliana, Yuliana (Journal of Community Empowerment for Health, 2024)
Introduction: Malpractice and medical case disputes are commonly found in the community. It was caused by misperception between patients and doctors in a medical case. Therefore, the informed consent role is essential for patients and doctors. This paper aims to describe the role of informed consent for patients and doctors. Methods: This is a narrative literature review. Literature was taken from PubMed, Google Scholar, and ScienceDirect. The selected journals were published within 10 years. Results: Informed consent is a sign of approval for any medical procedure that might cause disputes. On the doctors’ side, informed consent is a legal protection. On the other side, informed consent is an explanation for the patient in helping decide on approval or rejection of any medical procedure. An informed consent paper has legal protection for the attending physician. Doctors must give accurate and complete information about the procedure before it is done. Patients have the right to have an explanation, give consent, or rejection regarding any procedure. When a doctor does a medical procedure before giving informed consent, it is considered malpractice. Informed consent is related to human rights fulfillment. Patients have the right to accept or reject any medical procedure after the doctors explain thoroughly about the procedure. Conclusion: In conclusion, the role of informed consent for doctors is legal protection and obligation. Meanwhile, the role of informed consent for the patients is to fulfill human rights.